The Relationship between Mental Rotation and Figural Flexibility In a sample of 11th Grade Secondary Students in Damascus (Journal of Hama University, 2020)
The purpose of this research is to identify the nature of the relationship between Mental Rotation and Figural Flexibility, in addition to identifying the differences according to gender and the academic orientation (scientific- literary- vocational) in the above variables. To achieve these goals, The researcher used the Mental Rotation test (Vandenberg, 1971), and a factor-referenced cognitive test (Ekstrom, et al, 1976) is Figural Flexibility.The sample is consisting of 180 students of 11th grade secondary students in Damascus, (90 males and 90 females), (60 scientific/ 60 literary/ 60 Vocational students). The results showed: 1 - There is a positive Correlation between Mental Rotation and Figural Flexibility. 2 - gender variable: There were no differences in the Mental Rotation test, while differences in Figural Flexibility in favor of males.3 - The academic orientation (scientific- literary- vocational): there were differences in Mental Rotation for the academic orientations of the scientific and vocational, while differences in Figural Flexibility for the benefit academic orientations of the scientific.